Analysis of Speech Acts in the Short Story Laila by Putu Wijaya - Grace Ananda Togatorop; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
Literary work is the result of a work or creation composed by a writer to express feelings, experiences, and thoughts. Literary work is an imaginative work that uses beautiful language and is made in written form and arranged in a form that has artistic value. Imagination in literary works is imagination based on reality that is imagined by other people to become a beautiful composition. Short stories or short stories are one of the types included in literary works. Short story is a type of prose. Every literary work can be analyzed and studied using its own study. In this study, the aim is to look at the speech acts used in the short story entitled Laila by Putu Wijaya using pragmatic studies, using qualitative research methods. Qualitative descriptive research method is a research method used to examine the condition of the object where the researcher is the key instrument. The results of the research analysis of the object used show that pragmatic speech acts are divided into 3 parts, namely: (1) locutionary speech acts; (2) illocutionary speech acts, and (3) perlocutionary speech acts in the short story.